METHODOLOGY OF TEACHING LEXICON IN ENGLISH TO ELEMENTARY SCHOOL STUDENTS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This thesis provides a comprehensive overview of effective methodologies for teaching the lexicon in English to elementary school students, incorporating interesting strategies, multisensory approaches, and interactive activities tailored to the developmental stage of beginner learners.